Trois approches d’Hédi Bouraoui - Chapouthier, Georges (Revue CMC Review, 2016)
Georges Chapouthier describes and analyzes three approaches to Hédi Bouraoui’s work: Rafik Darragi’s recent book, Hédi Bouraoui: la parole autre; Mohammed Habib Samrakandi’s more intimate interview with Bouraoui, in a special issue of Horizons Maghrébins; and Bouraoui’s recent work, Mutante, la Poésie, which distills the essence of Bouraoui’s evolution as a poet-critic-theoretician.